2006
DOI: 10.1063/1.2172358
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of high current fully stripped carbon ion beam by direct injection scheme

Abstract: Acceleration of a 17 mA, 100 keV/ u C 6+ ion beam has been successfully achieved with an radio frequency quadrupole ͑RFQ͒ linac by means of "direct injection scheme." The C 6+ beam produced by a laser ion source with a Nd:YAG laser was injected to the high current RFQ linac. It has been experimentally proved that the fully stripped carbon ion beam with a current more than 10 mA was accelerated by the RFQ linac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…High ion yield per laser pulse can be generated. With a relatively small Nd:YAG laser (wavelength 1064 nm, 15 ns pulse width, 400 mJ pulse energy), it is possible to generate ~8x10 9 C 6+ ions/pulse [27].…”
Section: 1faraday Cup and Three-electrode Retarding Field Analyzermentioning
confidence: 99%
“…High ion yield per laser pulse can be generated. With a relatively small Nd:YAG laser (wavelength 1064 nm, 15 ns pulse width, 400 mJ pulse energy), it is possible to generate ~8x10 9 C 6+ ions/pulse [27].…”
Section: 1faraday Cup and Three-electrode Retarding Field Analyzermentioning
confidence: 99%
“…The C 6+ ion beam with a current more than 10 mA was accelerated by the RFQ linac. 19 The ion yield of the laser ion source depends on the laser pulse energy, pulse width, spot size, and target material. The charge separation from the laser plasma can be achieved by creating a uniform ion-accelerating external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…14 Laser ablation was previously used to generate carbon MCIs. [15][16][17][18][19][20] Kashiwagi et al reported the observation of fully stripped C 6+ ions using Nd:YAG (λ = 1064 nm, τ = 15 ns, pulse energy = 400 mJ, and intensity = 1.6 × 10 11 W cm −2 ). The ions were injected into a radio frequency quadruple linac.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of C 6+ ions injected into the linac was 6.0 × 10 9 with a current of 17 mA. 15 Emission of C MCIs was reported for CO 2 laser (λ = 10.6 µm, τ = 85 ns, and fluence of 1.2 J cm −2 ). 16 An electrostatic deflector ion filter was used to analyze the carbon ions with ion charge up to C 5+ reported.…”
Section: Introductionmentioning
confidence: 99%